Environmental efficiency of strengthening schemes for concrete beams with externally bonded fibre reinforced plastic composites. Issue 1 (2nd January 2019) - Xie, Hui-Bing; Wang, Yuan-Feng; Gucunski, Nenad; Wang, Rui; Wang, Jing-Jing; Wang, Zhong-Hao
Abstract: Externally bonded fibre reinforced plastic (FRP) is one of the most widely used methods in engineering practice to strengthen in-service reinforced concrete (RC) structures. Although some specifications, such as GB50367-2013 (China) and ACI440-2008 (U.S.A), have been issued to guide the design of strengthening schemes, few researches were conducted to evaluate environmental impacts of the strengthening schemes. This study aims to explore the environmental impact of FRP strengthened RC beam considering the structural safety and uncertainty, and to establish sustainable design criteria. Environmental impact and improvement of structural safety of two strengthening schemes designed according to the specifications of China (GB50367-2013) and U.S.A. (ACI440-2008) were evaluated by Life Cycle Assessment (LCA) method and reliability method, respectively. An environmental-efficiency index was introduced by taking an increment of safety as a functional unit in the LCA method. Furthermore, the allowable environmental impact was assumed and uncertainties involved in the LCA method were considered. The exceedance probability, denoting the possibility that environmental impact of a design scheme exceeds a presumed allowable value, is presented and calculated. It can be found that the environmental-efficiency indices of two schemes are close to each other. Moreover, the exceedance probability depends on the allowable environmental impact, thus it should be determined cautiously.